Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Pada Perusahaan LQ45 Yang Terdaftar Di BEI - Umi Kalsum (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to examine and analyze the effect of financial ratios as proxied by current ratio (CR), debt to equity ratio (DER), gross profit margin (GPM), net profit margin (NPM) and return on assets (ROA) on profit growth. in LQ45 companies listed on the IDX with the period 2018 to 2020. The samples in this study were all LQ45 companies listed on the IDX. The research method used classical assumption test to analyze data and linear regression analysis to test the data results. The results of this study indicate that the current ratio (CR) and return on assets (ROA) have a significant effect on earnings growth. Meanwhile, the debt to equity ratio (DER), gross profit margin (GPM), net profit margin (NPM) did not have a significant effect on profit growth.